Using Accreditation to Build Teamwork in a Department - David A Line (Academic Chairpersons Conference Proceedings, 2020)
The additional demands of the accreditation process provide a unique opportunity for program chairs to develop positive relationships between administration, staff, and faculty. This best practice presentation will look at the accreditation process from the perspective of the support staff and utilizing the accreditation process as a team building exercise.
Keywords: Leadership; Team building; Collaboration; Interpersonal communication